Antidepressants block effect of D‐cycloserine in OCD treatment. Issue 12 (December 2015) - Unknown
Abstract : The effects of the partial N‐methyl‐D‐aspartate (NMDA) agonist D‐cycloserine in augmenting cognitive behavioral therapy (CBT) in patients with obsessive‐compulsive disorder (OCD) were blocked in individuals taking an antidepressant concurrently, a new study has found. Concomitant antidepressant use did not have any effect in a group of patients receiving placebo in the study.